Digital flipbook module in circulatory system to facilitate student different intelligent and learning style - Rida Oktorida Khastini; Mila Ermila Hendriyani; Mahrawi Mahrawi; Nurul Hayat Hibatullah (Biosfer: Jurnal Pendidikan Biologi, 2023)
Students acquire and improve various intellectual abilities through learning process facilitated by learning methods. The study provides information on the development process of digital flipbook modules to facilitate student intelligence and learning style for the circulatory system, determine its feasibility, and students’ responses. The method used was an R&D with 4D development models. It consisted of four stages: define, design, develop, and disseminate. However, this research was limited to the development stage. Development of digital flipbook modules based on nine types of intelligence: linguistic, mathematical logic, kinesthetic, visual-spatial, musical, interpersonal, intrapersonal, naturalist, and existential. The instruments used expert feasibility questionnaires (materials and media) and student response questionnaires. The result of the assessment test of experts in the material aspect was 96.4% in the very eligible category, and the media aspect was 92.8% in the very suitable category. The score of students’ responses was 90,14%, in the very eligible category. Based on the analysis results, the digital flipbook module was suitable biology teaching material for the circulatory system